Współczesne słuchowisko o charakterze poetyckim i jego obecność w ramówce radiowej = A contemporary drama of a poetic nature and its presence in the radio schedule - Łastowiecki, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
summary: In the text the audio compositions made specifically for the radio have been separated from the radio drama format. A proposed definition of a radio sub genre draws from theater propositions, as well as linguistic. Taking into consideration the schedule changes at the Polish Radio, the text discusses the poetic radio dramas of the most important radio authors from the last few decades.
Keywords: oryginalne słuchowisko poetyckie; słuchowisko radiowe; dramaturgia radiowa; radio artystyczne; fabuła wewnętrzna; original poetic radio drama; radio drama; radio dramaturgy; artistic radio; inner plot